Batch and continuous flow asymmetric synthesis of anabolic-androgenic steroids via a single-cell biocatalytic Δ1-dehydrogenation and C17β-carbonyl reduction cascade. Issue 8 (4th April 2023) - Zhang, Yajiao; Liu, Minjie; Yang, Zixin; Lin, Juan; Huang, Zedu; Chen, Fener
Abstract : Asymmetric synthesis of (+)-boldenone and (+)-boldenone undecylenate was achieved in batch and continuous flow, using an enzyme cascade process catalyzed by an engineered Δ 1 -KstD and a mined 17β-CR. Abstract : Chemoenzymatic asymmetric synthesis of an anabolic-androgenic steroid (+)-boldenone (3 ) and its prodrug (+)-boldenone undecylenate (4 ) was accomplished starting from commercially available 4-androstene-3, 17-dione (4-AD, 1 ) under both batch and continuous flow conditions. The key feature of the current synthesis is the construction of an enzymatic cascade process in a single Escherichia coli cell for straightforward synthesis of (+)-boldenone (3 ), enabled by the combined action of ReM2 (I51L/I350T), an engineered 3-ketosteroid-Δ 1 -dehydrogenase (Δ 1 -KstD) possessing 5-fold and 3-fold higher Δ 1 -dehydrogenation activity towards 4-AD and testosterone (2b ) relative to the wild-type Δ 1 -KstD, respectively, and 17β-CR, a newly mined carbonyl reductase from Empedobacter stercoris showing strong C17-carbonyl reduction activity. With the optimal reaction conditions established for mutual tolerance between ReM2 and 17β-CR, complete conversion of 4-AD into (+)-boldenone was first realized in a conventional batch mode with a space-time yield (STY) of 1.09 g L −1 h −1 . Furthermore, this single cell-catalyzed synthesis of (+)-boldenone was successfully implemented in continuous flow, achieving an order of magnitude higher STY (10.83 g L −1 h −1 ) than that for batch synthesis, which also represents the highest record for the biocatalytic synthesis of (+)-boldenone reported to date. Finally, (+)-boldenone undecylenate (4 ) was produced in a fully continuous flow mode with an overall yield of 75%, through telescoping the newly developed biocatalytic Δ 1 -dehydrogenation/17β-carbonyl reduction cascade with the follow-up esterification reaction. The present work not only provides a concise, efficient, and sustainable avenue for the asymmetric synthesis of (+)-boldenone and (+)-boldenone undecylenate, but also showcases the effectiveness and great potential of flow biocatalysis in the production of value-added compounds.